2004
DOI: 10.1074/jbc.m409203200
|View full text |Cite
|
Sign up to set email alerts
|

Global Analysis of Protein Sumoylation in Saccharomyces cerevisiae

Abstract: Although the modification of cellular factors by SUMO is an essential process in Saccharomyces cerevisiae, the identities of the substrates remain largely unknown. Using a mass spectrometry-based approach, we have identified 271 new SUMO targets. These substrates play roles in a diverse set of biological processes and greatly expand the scope of SUMO regulation in eukaryotic cells. Transcription appears to be the most prevalent process associated with sumoylation with novel SUMO substrates found in basal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
312
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 294 publications
(339 citation statements)
references
References 38 publications
(38 reference statements)
25
312
2
Order By: Relevance
“…Among them are the existence of a nucleolus-resident E3 SUMO ligase Mms21p (Zhao and Blobel 2005), the localization of two mammalian SUMOisopeptidases to the nucleolus (Mukhopadhyay and Dasso 2007), and especially by proteomic data in budding yeast (Wohlschlegel et al 2004;Hannich et al 2005). Indeed, among the 196 nuclear sumoylated proteins that have at least two sumoylated sites in vivo (Wohlschlegel et al 2004), 39 are nucleolar (according to GO), 41 are confirmed to be partially nucleolar, 90 are chromatin components that can potentially have a nucleolar subset, six are SUMO pathway components, and only 20 are uncharacterized or unlikely to be nucleolar. Although the hypothesis of polysumoylation's role in nucleolar targeting needs additional extensive validation, its emergence highlights the usefulness of the improved SUMO fusion approach (CSM), both for practical application to a given SUMO target and for advancement of general knowledge about SUMO biology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them are the existence of a nucleolus-resident E3 SUMO ligase Mms21p (Zhao and Blobel 2005), the localization of two mammalian SUMOisopeptidases to the nucleolus (Mukhopadhyay and Dasso 2007), and especially by proteomic data in budding yeast (Wohlschlegel et al 2004;Hannich et al 2005). Indeed, among the 196 nuclear sumoylated proteins that have at least two sumoylated sites in vivo (Wohlschlegel et al 2004), 39 are nucleolar (according to GO), 41 are confirmed to be partially nucleolar, 90 are chromatin components that can potentially have a nucleolar subset, six are SUMO pathway components, and only 20 are uncharacterized or unlikely to be nucleolar. Although the hypothesis of polysumoylation's role in nucleolar targeting needs additional extensive validation, its emergence highlights the usefulness of the improved SUMO fusion approach (CSM), both for practical application to a given SUMO target and for advancement of general knowledge about SUMO biology.…”
Section: Discussionmentioning
confidence: 99%
“…Elimination of all three E3 activities (Siz1, Siz2, and Mms21) is synthetically lethal (Reindle et al 2006). While recent proteomic studies demonstrated that several hundreds of proteins can be modified in vivo (Panse et al 2004;Wohlschlegel et al 2004;Zhou et al 2004;Denison et al 2005;Hannich et al 2005;Wykoff and O'Shea 2005), direct evidence of biological significance and/or functional importance of these modifications is lacking for most substrates. Two main obstacles prevent the elucidation of the sumoylation's role for a given target protein using straightforward biochemical or genetic methods.…”
Section: Introductionmentioning
confidence: 99%
“…Among these targets might be components of the sumoylation machinery, i.e. E1-3, as they are known to be SUMO modified (Wohlschlegel et al, 2004). This may partially explain the global deregulation of sumoylation in STUbL mutants.…”
Section: Discussionmentioning
confidence: 99%
“…However, while HDAC sumoylation regulates a number of gene regulatory pathways in mammalian cells, in S. cerevisiae, proteomic analyses of sumoylated proteins indicate that HDACs are not a robust target (Wohlschlegel et al 2004;Zhou et al 2004;Hannich et al 2005), although Hda1 was detected in one SUMO proteomic analysis (Panse et al 2004). Our findings that substitution mutations in histone sumoylation sites increase transcription, and that SUMO fused to histones is repressive to transcription, strengthen the first two models of direct effect of histone sumoylation through either competition with acetylation or recruitment of HDACs (i.e., the first and second proposed mechanisms), rather than an indirect effect through altering HDAC activity (i.e., the third mechanism).…”
Section: Discussionmentioning
confidence: 99%
“…Recent genomic studies aimed at identifying cellular substrates for sumoylation indicate that many are involved in transcription regulation and include transcription factors, transcription machinery proteins, and components that modify chromatin structure (Manza et al 2004;Wohlschlegel et al 2004;Zhou et al 2004;Hannich et al 2005). In most cases, sumoylation of transcriptional activators results in transcriptional repression (Gill 2003;Hay 2005).…”
mentioning
confidence: 99%